The higher functional field : evidence from northern Italian dialects - Poletto, Cecilia, 1962- (Oxford studies in comparative syntax., 2000)
This work investigates the syntax of the higher portion of the functional structure of the clause using comparative data from hundreds of Northern Italian dialects. The area contains dialects that are different in most ways yet homogenous syntactically, making it ideal for this type of analysis.